Social isolation and cardiovascular health in US adults - Kieu, Chi; Behforooz, Susan; Wong, Nathan Donald (Scripta Medica, 2020)
Background. The relation of social isolation (SI) to global cardiovascular health (CVH) is not clear. We examined the association of CVH metrics to SI within US adults.Methods. Using the US National Health and Nutrition Examination Survey, we examined the association of SI with American Heart Association’s Life’s Simple 7 (LS7) CVH components (smoking, body mass index, physical activity, total cholesterol, diet, blood pressure, fasting blood glucose).  The sum of the  components (scored 1 for poor, 2 for intermediate, and 3 for ideal) created a composite CVH score.  Multiple logistic regression provided the odds of SI according to levels of the LS7 components adjusted for age, sex, and ethnicity.Results. We studied 3528 adults aged ³40 years. The mean age, sex, and ethnicity-adjusted composite CVH score was 14.1 vs. 14.6 in those with vs. without SI (p